1
$\begingroup$

Let $R$ be a euclidean domain, $m_0,\ldots ,m_{k-1}\in R$ be pairwise coprime and $m:=m_0\cdots m_{k-1}$. The Chinese remainder theorem states: $$\varphi:R\to R/(m_0)\times\cdots \times R/(m_{k-1})\;,\;\;\;\alpha\mapsto \left(\kappa_0(\alpha),\ldots,\kappa_{k-1}(\alpha)\right)$$ is a surjective ring homomorphism, where $$\kappa_i:R\to R/(m_i)\;,\;\;\;\alpha\mapsto \alpha\text{ mod }m_i$$ is the canonical isomorphism, and thereby induces an ring isomorphism $$R/(m)\to R/(m_0)\times\cdots \times R/(m_{k-1})$$


This result can be transferred to the special case $R=\mathbb{K}[X]$, where $\mathbb{K}$ is a field. Therefore, let $\xi_0,\ldots, \xi_{k-1}\in\mathbb{K}$ be pairwise distinct and $m_i:=X-\xi_i$ (thus, $m_0,\ldots,m_{k-1}$ are pairwise coprime).

How exactly does the existence of a ring isomorphism $$\chi:\mathbb{K}[X]/(m)\to\mathbb{K}^n\;,\;\;\;f\text{ mod }m\mapsto \left(f(\xi_0),\ldots,f(\xi_{k-1})\right)$$ follow from the Chinese remainder theorem? I can't see it. Please explain it by using the notion in the statement of the Chinese remainder theorem above.

$\endgroup$
  • $\begingroup$ @user26857 Sorry, what I meant was "distinct". $\endgroup$ – 0xbadf00d Aug 25 '14 at 11:12
3
$\begingroup$

If $\xi_1\ldots,\xi_k$ are pairwise distinct, then the ideals $(x-\xi_1),\ldots,(x-\xi_k)$ are pairwise coprime, and by the theorem we have an isomorphism$$\chi:\mathbb{K}[x]/\Pi (x-\xi_i)\to\prod\mathbb{K}/(x-\xi_i)\simeq\mathbb{K}^k.$$ The only thing left to be said is that for any polynomial $f\in\mathbb{K}[x]$ and for any $\xi\in\mathbb{K}$ we have $f-f(\xi)\in(x-\xi)$ (see explanation below), or in other words, when dividing $f$ by $(x-\xi)$ the remainder is equal to $f(\xi)$. Thus the canonical map $\mathbb{K}[x]\to\mathbb{K}[x]/(x-\xi)\simeq\mathbb{K}$ is given by $f\mapsto f(\xi)$.

We explain why $f-f(\xi)\in(x-\xi)$. Denote $g=f-f(\xi)$, and immediately get $g(\xi)=0$. Since $\mathbb{K}[x]$ is Euclidean, we can write $g=p(x-\xi)+r$, where $r$ has degree smaller than that of $(x-\xi)$. As the latter is linear, $r$ is a constant. As $g(\xi)=0,$ the previous equation implies $r=0$, thus $$f-f(\xi)=g=p(x-\xi)\in(x-\xi).$$

$\endgroup$
  • $\begingroup$ For any $f\in\mathbb{K}[X]$ and for any $\xi\in\mathbb{K}$ we have $$f-f(\xi)\in (X-\xi)$$ That's the whole point. I don't understand why this holds. $\endgroup$ – 0xbadf00d Aug 25 '14 at 10:01
  • $\begingroup$ I added an explanation to the answer, check it out. $\endgroup$ – Amitai Yuval Aug 25 '14 at 10:18
  • $\begingroup$ That was easy. Thanks a lot. $\endgroup$ – 0xbadf00d Aug 25 '14 at 10:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.